ANALISIS PENGARUH PDRB PER KAPITA DAN JUMLAH TENAGA KERJA TERHADAP JUMLAH PENDAPATAN PAJAK DAERAH PROVINSI DI INDONESIA - Susila, Muktar Redy; Pradhani, Fastha Aulia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
The purpose of this study is to analyze the effect of GRDP per capita and the labor number on the province tax revenue. Regional tax revenues for each province have different figures. It is suspected that GRDP per capita and number of labor affect local tax revenues. To answer the research hypothesis, multiple linear regression analysis was used. The data used in the study were sourced from the Badan Pusat Statistik in 2020. The dependent variable in this study is local tax revenue, while the independent variables are GRDP per capita and the number of labor. Based on the results of the t-test, it was found that the GRDP per capita and the number of workers had a significant effect on province regional tax revenues. The coefficient value of GRDP per capita and the number of labor is positive. Based on the multiple linear regression model formed, the R2 value is 91.05%. So it can be said that GRDP per capita and the number of labor can explain the province tax revenue of 91.5%, the remaining 8.5% is explained by other independent variables not included in this study.